Cloud native integration with Apache Camel : building agile and scalable integrations for Kubernetes platforms - Camposo, Guilherme (Apress L.P., 2021)
Address the most common integration challenges, by understanding the ins and outs of the choices and exemplifying the solutions with practical examples on how to create cloud native applications using Apache Camel. Camel will be our main tool, but we will also see some complementary tools and plugins that can make our development and testing easier, such as Quarkus, and tools for more specific use cases, such as Apache Kafka and Keycloak. You will learn to connect with databases, create REST APIs, transform data, connect with message oriented software (MOMs), secure your services, and test using Camel. You will also learn software architecture patterns for integration and how to leverage container platforms, such as Kubernetes. This book is suitable for those who are eager to learn an integration tool that fits the Kubernetes world, and who want to explore the integration challenges that can be solved using containers. You will: Focus on how to solve integration challenges Understand the basics of the Quarkus as it's the foundation for the application Acquire a comprehensive view on Apache Camel Deploy an application in Kubernetes Follow good practices.